Long-Term Relief of Painful Bladder Syndrome by High-Intensity, Low-Frequency Repetitive Transcranial Magnetic Stimulation of the Right and Left Dorsolateral Prefrontal Cortices - Nizard, Julien; Esnault, Julien; Bouche, Bénédicte; Suarez Moreno, Alcira; Lefaucheur, Jean-Pascal; Nguyen, Jean-Paul (Frontiers in Neuroscience, 2018)
Aims: To show the value of low-frequency repetitive transcranial magnetic stimulation (rTMS) of the dorsolateral prefrontal cortex (DLPFC) to treat bladder pain syndrome (BPS), characterized by suprapubic pain, urgency and increased micturition frequency. Methods: A 68-year-old woman with BPS underwent 16 sessions of high-intensity, low-frequency (1 Hz) rTMS of the DLPFC, first on the right hemisphere (one daily session for 5 days, followed by one weekly session for 5 weeks), and then on the left hemisphere (one monthly session for 6 months). Results: At the end of the rTMS protocol, suprapubic pain completely vanished, micturition frequency dramatically decreased (by 60-80%), while fatigue and sleep quality improved (by 57-60%). The patient reported an overall satisfaction rate of 80% and her activities of daily living tending to normalize. Conclusions: This is the first report showing that high-intensity, low-frequency rTMS delivered on the DLPFC region of both hemispheres can relieve most symptoms of BPS (pain, urinary symptoms, and interference with physical functioning) in clinical practice.